Detection of blaTEM, blaOXA, blaCTX-M, and blaSHV genes of antibiotic resistance in diarrheagenic E. coli causing enteric infection in hypertensive patients at Laquintinie Hospital, Littoral Region of Cameroon - Ornella Djiolieu Tsobeng; Armelle T. Mbaveng; Michael F. Kengne; Ballue S.T. Dadjo; Delano G.T. Fonjou; Victor Kuete (Journal of Infection and Public Health)
Background: Pathogenic Escherichia coli is one of the most common causes of acute watery diarrhea among children and adults in the developing world. The severity of infection by this bacterium is a product of many factors, including virulence properties and antimicrobial resistance. This study aimed to determine the distribution of different virulence genes of E. coli isolates in hypertensive and non-hypertensive patients and their association with some selected beta-lactam resistance genes. Methods: At the Douala Laquintinie Hospital, 518 fecal samples were collected from both hypertensive and non-hypertensive patients with enteric infections. E. coli was isolated on eosin-methylene blue agar (EMB) and identified by the Api 20 E Galery. The virulence genes and extended-spectrum β-lactamase-producing (ESBL) E. coli genes were detected by simplex polymerase chain reaction (PCR), while antimicrobial susceptibility was tested by the Kirby-Bauer agar disc diffusion method. Results: The prevalence of enteric infection due to diarrheagenic E. coli (n = 204) was found to be 39.38 % in the general population (n = 518). There were 55 enterovirulent E. coli isolates identified. According to hypertension (HTN), enteropathogenic E. coli (EPEC) isolates were more isolated in hypertensive patients (77.78 %) than in non-hypertensive patients (22.22 %), while enteroaggregative E. coli (EAEC) were the most frequent in non-hypertensive patients (58.33 %). EPEC, EAEC, enterotoxigenic E. coli (ETEC), and Shiga toxin-producing E. coli (STEC) isolates showed higher rates of resistance to amoxicillin (AMO) (90.48 %; 100.00 %; 100.00 %; 100.00 % vs 83.33 %; 85.71 %; 75.00 %; 50.00 %) and SXT (71.43 %; 80.00 %; 75.00 %; 75.00 % vs 0.00 %; 28.57 %; 50.00 %; 25.00 %) in hypertensive patients compared to non-hypertensive patients. The prevalence of ESBL-producing (ESBL-P) E. coli was 87.27 %. The resistance genes blaTEM (64.71 % vs 52.38 %) and blaOXA (23.53 % vs 9.52 %) were more frequently detected in hypertensive patients than in non-hypertensive patients. The high resistance to AMO was correlated with the presence of the blaCTX-M gene (OR: 5.52; 95 % CI: 0.61–49.39; p = 0.093). Conclusion: This study reveals the high burden of the typical EPEC, EAEC, and ESBL-P E. coli and confirmed the high occurrence of blaCTX-M and blaTEM among ESBL-producing E. coli in hypertensive patients. The study suggests that measures need to be taken to reduce the harmfulness of enterovirulent E. coli and the resistance of enterovirulent E. coli in hypertensive patients.